Effects of flipped classrooms integrated with MOOCs and game-based learning on the learning motivation and outcomes of students from different backgrounds. Issue 8 (17th November 2019) - Hung, Cheng-Yu; Sun, Jerry Chih-Yuan; Liu, Jia-Yin
ABSTRACT: This study aimed to investigate the effect of flipped classrooms integrated with massive open online courses (MOOCs) and game-based learning on the learning motivation and learning outcomes of students from different backgrounds (in terms of gender, grade, self-confidence indicators in mathematics, and roles played in the game-based learning process). Surveys and a semi-structured open questionnaire were used for data collection, including a basic information questionnaire (to understand the participants' backgrounds), a questionnaire on learning motivation (the Motivated Strategies for Learning Questionnaire, MSLQ), a test of learning achievements in mathematics, and a semi-structured open-ended questionnaire (to understand the learners' feelings). Quantitative analysis results showed that flipped classrooms integrated with MOOCs and game-based learning can enhance students' learning motivation and outcomes. Specifically, compared with students with high self-confidence in learning mathematics, students with low and medium levels of self-confidence showed significantly greater improvement in overall learning motivation. Significantly more enhancements were found for the expectation component of "soldiers" (students with relatively lower learning achievements) than for "generals" (students with higher learning achievements). Furthermore, students in the eighth grade showed significantly greater progress in academic performance than did students in the seventh grade.